Strategi Summarizing dalam Meningkatkan Pemahaman Bacaan pada Kelas Extensive Reading - siti mafulah (JURNAL ILMIAH BAHASA DAN SASTRA, 2020)
The aims of this paper were to depict how the implication of summarizing strategy on students’ reading comprehension and how the implication of summarizing strategy can improve the reading comprehension. This research was descriptive qualitative using observation, interview and questionnaire as instrument in gathering the data. The participants of this research were 26 students of English department of Universitas Kanjuruhan Malang who joined Extensive Reading class. The steps in gathering the data, the students were asked to read the 5 minutes everyday, the topic was free based on students’ preferences. After reading, they have to make a summary in their reading journal. The students’ progress will be reported once a week. They have to retell their understanding to their friends in the classroom. The result showed that the students comprehension raised from week to week. It can be indicated from the result of students’ summary in week 1. They tended to copy and paste the reading text in their reading journal. The progress can be seen after they did summarize in week-5. Students tended to write the content of the text based on their own words. It means through applying strategy summarizing, students can improve their reading comprehension well. Based on the questionnaire result, students were motivated to read more. It can be concluded that using summarizing as strategy in reading increases students’ reading comprehension.